2017
DOI: 10.1177/1940082917710617
|View full text |Cite
|
Sign up to set email alerts
|

Twigs in the Leaf Litter as Ant Habitats in Different Vegetation Habitats in Southeastern Brazil

Abstract: Vegetation structure and microhabitat availability and diversity affect ant assemblage diversity, growth, and dispersal. In this study, we described assemblages of ants nesting in twigs found in the leaf litter, comparing nest characteristics and ant colony sizes among different vegetation habitats at a regional scale. Twigs were collected in urban parks, Eucalyptus plantations, and preserved areas of native Atlantic Forest. We measured the twigs, counted the number of ant colonies, and estimated canopy openne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 51 publications
2
17
0
3
Order By: Relevance
“…Of these, only L. neotropicum (Mann-Whitney = 1.7401; p = 0.0818) and P. sospes (Mann-Whitney = 0.0985; p = 0.9215) colonized similar-diameter twigs in different vegetation habitats (Fig 2), although the leaf litter in the native forest shelters a higher twig diversity (Murnen et al, 2013) compared to eucalyptus plantations (Pereira et al, 2007). Our study is the first to compare "common inhabitants" of twigs among different vegetation habitats in the Brazilian Atlantic domain, demonstrating that these communities are affected by habitat structure, as shown by Souza-Campana et al (2017) for other twig-colonizing ant species. By finding that 25% of the "common inhabitants" were arboreal ants, and that some species colonized similar twigs in different vegetation habitats, our results contribute to the knowledge of the biology of these ants in the leaf litter.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…Of these, only L. neotropicum (Mann-Whitney = 1.7401; p = 0.0818) and P. sospes (Mann-Whitney = 0.0985; p = 0.9215) colonized similar-diameter twigs in different vegetation habitats (Fig 2), although the leaf litter in the native forest shelters a higher twig diversity (Murnen et al, 2013) compared to eucalyptus plantations (Pereira et al, 2007). Our study is the first to compare "common inhabitants" of twigs among different vegetation habitats in the Brazilian Atlantic domain, demonstrating that these communities are affected by habitat structure, as shown by Souza-Campana et al (2017) for other twig-colonizing ant species. By finding that 25% of the "common inhabitants" were arboreal ants, and that some species colonized similar twigs in different vegetation habitats, our results contribute to the knowledge of the biology of these ants in the leaf litter.…”
mentioning
confidence: 67%
“…None species was recorded in urban parks in 864 m 2 of leaf litter; in the eucalyptus plantations, four species (33.3%) were observed in 57 twigs (= 0.06 twigs/ m 2 of leaf litter); and in the native forest, 11 species (91.7%) in 217 twigs (= 0.25 twigs/m 2 of leaf litter). Other studies on ants that colonize twigs in native forest and agroecosystems (Murnen et al, 2013;Souza-Campana et al, 2017) have also shown that the less the anthropogenic influence, for the best the ant diversity.…”
mentioning
confidence: 92%
See 3 more Smart Citations